Electroreductive Deoxygenative C−H and C−C Bond Formation from Non‐Derivatized Alcohols Fueled by Anodic Borohydride Oxidation - Dr. Piret Villo; Malin Lill; Zainab Alsaman; Adrian Soto Kronberg; Victoria Chu; Dr. Guillermo Ahumada; Dr. Hemlata Agarwala; Prof. Mårten Ahlquist; Ass. Prof. Helena Lundberg (ChemElectroChem, 2023)
Abstract Alcohols are one of the most common organic compound classes among natural and synthetic products. Thus, methods for direct removal of C−OH groups without the need for wasteful pre‐functionalization are of great synthetic interest to unlock the full synthetic potential of the compound class. Herein, electroreductive C−OH bond activation and subsequent deoxygenative C−H and C−C bond formation of benzylic and propargylic alcohols are demonstrated along with mechanistic insights. Experimental and theoretical studies indicate that the reductive C−OH bond cleavage furnishes an open shell intermediate that undergoes a radical‐polar crossover to the corresponding carbanion that subsequently undergoes protonation to furnish alkane products. Furthermore, we demonstrate that the carbanion can be trapped with CO2 to form arylacetic acids. The cathodic transformations are efficiently balanced by the anodic oxidation of sub‐stoichiometric borohydride additives, a strategy that serves as a highly attractive alternative to the use of sacrificial metal anodes.